2023
DOI: 10.3390/ani13152486
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Canine and Feline Mortality during Anaesthesia at a University Clinic in Greece

Konstantinos Varkoulis,
Ioannis Savvas,
Tilemachos Anagnostou
et al.

Abstract: This retrospective cohort study investigated the mortality rate during anaesthesia and possible contributing factors in canine and feline population in an academic institution in Greece. Data on 1187 dogs and 250 cats which underwent general anaesthesia from 1 January 2018 to 31 December 2019 at the Veterinary Faculty of the Aristotle University of Thessaloniki were analysed regarding cardiac arrest and mortality. In dogs, the rate of cardiac arrest was 1.1% and the rate of death was 0.6%. In cats, these rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
1
1
Order By: Relevance
“…Our study's more significant proportion of high‐risk patients might explain the differences observed. However, other studies including a high proportion of ASA III‒IV patients showed a higher risk of anaesthetic‐related death than found in our study 18–21 . The random inclusion of centres throughout the project and the extended duration of case solicitation may potentially influence the population characteristics and, consequently, the death rate.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our study's more significant proportion of high‐risk patients might explain the differences observed. However, other studies including a high proportion of ASA III‒IV patients showed a higher risk of anaesthetic‐related death than found in our study 18–21 . The random inclusion of centres throughout the project and the extended duration of case solicitation may potentially influence the population characteristics and, consequently, the death rate.…”
Section: Discussioncontrasting
confidence: 65%
“…This observation has been particularly noted in human anaesthesia studies, specifically when comparing developed and developing regions 31 . Some studies have focused on specific hospitals, providing meaningful information that may only be relevant to those centres 1,18,28,32,33 . In contrast, the current research provides a global perspective by collecting data from multiple clinics, including primary care and referral centres.…”
Section: Discussionmentioning
confidence: 99%